The Relationship Between Mother's Knowledge Levels Of Diarrhea And Prevention And Handling In Children - Asdinar; Irmawati (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2017)
Based on data from the World Health Organization (WHO) in 2013 Diarrhea is the second disease that causes death in children and kills 1.5 million children every year. According to the UNICEF report on September 13, 2013, around 150,000 Indonesian children every year and every day in Indonesia more than 400 children die from diarrhea. The purpose of this study was to determine the relationship of maternal knowledge about diarrhea with the prevention and treatment of diarrhea in children in the working area of ​​Public Health. Quantitative research design with a cross-sectional design approach. How to collect data using a questionnaire. The study population is mothers who have children in the Bontobangun Health Center working area. A total of 58 mothers and 38 of them became the study sample. The sampling technique used is convenience sampling. The type of test used is the chi-square test alternative merge cell. The results of the analysis used a Chi-square statistical test with a level of confidence (ɑ = 0.05). Based on the results of this test, obtained the value of prevention is p = 0.303 and treatment p = 0.003 with ɑ <0.05). The results of this study are there is a relationship between the level of maternal knowledge with the prevention and treatment of diarrhea in children in the work area of ​​the Bontobangun Community Health Center. Bulukumba in 2017. The study concludes that most respondents have good knowledge so that it affects the prevention and treatment of children with diarrhea. The suggestion from this research is that the results of this study can be used as input for nurses, community nursing regarding the relationship of the level of knowledge with the prevention and treatment of diarrhea.